Bringing Again Noble Metal Nanoparticles to the Forefront of Cancer Therapy - Vlamidis, Ylea; Voliani, Valerio (Frontiers in Bioengineering and Biotechnology, 2018)
Nanomaterials have attracted increasing interest for their potentiality to revolutionize the diagnosis and treatment of many diseases, especially neoplasms. Interestingly, there is a huge imbalance between the number of proposed nanoplatforms and the few ones approved for clinical applications. This disequilibrium affects in particular noble metal nanoparticles (NPs), that present no-approved platform and very few candidates in clinical trials because the issue of persistence. In this perspective, we discuss if nanomedicine is generally keeping its promises with a focus on the approach that could fill the gap between NPs and oncology in the next future: the ultrasmall-in-nano.